The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00192-014-2571-y
|View full text |Cite
|
Sign up to set email alerts
|

Label-free, three-dimensional multiphoton microscopy of the connective tissue in the anterior vaginal wall

Abstract: MPM is a robust, rapid, and label-free method that can be used to quantify the collagen and elastin content in thick specimens of the vagina. It is an excellent tool for future three-dimensional studies of the extracellular matrix in patients with pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Sikora et al (2015) used samples of the anterior wall of the vagina from patients who had had a hysterectomy, which were preserved in one of four ways: i) in cold, ii) fresh without fixation, iii) with formaldehyde, and iv) with Thiel solution, to demonstrate the potential of multiphoton microscopy in the study and 3D analysis of the extracellular matrix of the pelvic organs, in which they detected collagen and elastin, for later comparison with standard histological methods. The authors found no differences in collagen and elastin volumes when comparing the samples from the four groups.…”
Section: Authorsmentioning
confidence: 99%
“…Sikora et al (2015) used samples of the anterior wall of the vagina from patients who had had a hysterectomy, which were preserved in one of four ways: i) in cold, ii) fresh without fixation, iii) with formaldehyde, and iv) with Thiel solution, to demonstrate the potential of multiphoton microscopy in the study and 3D analysis of the extracellular matrix of the pelvic organs, in which they detected collagen and elastin, for later comparison with standard histological methods. The authors found no differences in collagen and elastin volumes when comparing the samples from the four groups.…”
Section: Authorsmentioning
confidence: 99%
“…TPEF microscopy is commonly used to visualize and quantify elastic fibers in the dermis [22], but it cannot be considered a selective method because collagen and elastic fibers have broad and overlapping spectral profiles [23][24][25][26]. It is important to note that collagen autofluorescence is variable and depends on the characteristics of the studied tissues (skin, gastric and colonic mucosa [25], vaginal mucosa [27]) and the nature of pathological processes (normal scar, keloid [28], tumor tissue [29]). This is due to variation in spatial organization of collagen fibers [25], the type of collagen fibers [30,31] and the surrounding of collagen fibers by other components of the extracellular matrix [23,25].…”
mentioning
confidence: 99%